Prone position surgery for a professional sumo wrestler with thoracic ossification of the posterior longitudinal ligament resulting in intraoperative brachial plexus injury by hypertrophic pectoral muscles. (May 2019) - Saiwai, Hirokazu; Okada, Seiji; Kawaguchi, Ken-ichi; Saito, Takeyuki; Hayashida, Mitsumasa; Matsushita, Akinobu; Matsumoto, Yoshihiro; Nakashima, Yasuharu
Highlights: Surgery in the prone position is associated with a variety of complications. Muscular athletes pose a risk for brachial plexus injury during prone surgery. Brachial plexus injury occurs due to the compression by the pectoral muscles. Abstract: Surgery in the prone position is associated with a variety of complications due to the positioning, including the widely recognized peripheral nerve compression injuries and brachial plexus neuropathy. Previous studies have reported that thin body habitus is a predisposing risk factor for the compressive peripheral nerve injuries due to the prone position surgery. However, prone-position-related brachial plexus injury in patients who are overweight due to hypertrophic muscles have never been reported. Here we report a case of a professional sumo wrestler with severe thoracic ossification of the posterior longitudinal ligament (OPLL). Thoracic OPLL was successfully treated by posterior spinal fusion and decompression surgery. Despite a preoperative simulation and intraoperative inspection of the patient's surgical positioning, he suffered from bilateral upper extremity paralysis immediately after the surgery. Postoperative axillary MRI image revealed a high-intensity area on both sides of his pectoral muscles and axillary fossa, which implied that the pectoral muscles between the ribs and chest pad were pushed out toward the axillary fossa, resulting in compressive brachial plexus injury. His upper extremity motor paralysis was fully recovered in 6 months, but he still has mild tingling sensation even after 12 months of his surgery. In conclusion, overweight patients with hypertrophic muscles pose a risk for brachial plexus entrapment injury by pectoral muscles during prone-position surgery, and therefore it would be more effective to use a wide chest pad to reduce the pressure on the pectoral muscles to prevent it from being pushed out toward the axillary fossa.